(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
An experiment was conducted in wooden boxes to evaluate water use efficiency, biomass production, nitrogen and potassium uptake and yield of tomato plants (Lycopersicon esculentum) grown under flood irrigation (FI) and surface drip irrigation (SDI). Leaf area, leaf area index, biomass production and yield of tomato plants were significantly (P<0.05) higher in SDI than FI treatment. Biomass production (g/plant) was 53.3 and 42.2 and yield of tomato (kg/plant) was 1.27 and 0.99 in SDI and FI treatments, respectively. Surface drip irrigation increased water use efficiency (Kgm-3) of tomato plants by two fold (37.88) compared to flood irrigation ( 19.88). Significantly (P<0.05) higher concentrations of nitrogen in leaf (3.22%) and stem (2.62 %) were measured for tomato plants grown under SDI than FI (2.63 and 2.19 %). Potassium concentrations on the other hand, showed no significant differences. DOI: http://dx.doi.org/10.3329/jasbs.v38i2.15611 J. Asiat. Soc. Bangladesh, Sci. 38(2): 207-215, December 2012